2012
DOI: 10.1016/j.indcrop.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a phenological model for strategic decisions for hemp (Cannabis Sativa L.) biomass production across European sites

Abstract: The optimal combination of yield and quality of hemp fibres from field grown crops is around flowering. Therefore prediction of flowering time would support in planning production and optimization of the cultivar choice for different agro-ecological zones. In the current paper the validation of a recently published model (Amaducci et al., 2008a) is carried out for four varieties across a wide range of sites and thus of air temperature-photoperiod combinations. The model was evaluated by comparing its output to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…These variations can be explained by differences in photoperiod regimes across locations. Hemp is a short-day plant, and the length of the vegetative growth period depends on the shift from long-to short-day photoperiod regimes (Amaducci et al, 2012). The vegetative growth period is characterized by biomass production, after which this behavior shifts toward fiber maturation (secondary fiber formation and lignification) and plant reproduction during flowering development (Van Der Werf and Turunen, 2008;Liu et al, 2015).…”
Section: Fiber Quality Traits Are Extensively Diverse and Heritable Bmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations can be explained by differences in photoperiod regimes across locations. Hemp is a short-day plant, and the length of the vegetative growth period depends on the shift from long-to short-day photoperiod regimes (Amaducci et al, 2012). The vegetative growth period is characterized by biomass production, after which this behavior shifts toward fiber maturation (secondary fiber formation and lignification) and plant reproduction during flowering development (Van Der Werf and Turunen, 2008;Liu et al, 2015).…”
Section: Fiber Quality Traits Are Extensively Diverse and Heritable Bmentioning
confidence: 99%
“…Morphological measurements, fiber quality, and flowering traits of hemp respond strongly to environmental factors, particularly to photoperiod and temperature but also to soil composition and crop management (Faux et al, 2013;Amaducci et al, 2015;Sawler et al, 2015). Hemp is a short day plant, and its flowering time is influenced by changes in the photoperiod regime (Amaducci et al, 2012). In locations where the shift from long-day toward short-day photoperiod regimes occurs early, hemp plants flower early, whereas in locations where the shift occurs later, the critical photoperiod for flowering is reached later (reviewed in Salentijn et al, 2019).…”
mentioning
confidence: 99%
“…Breeding programs, especially after success in selection of low-THC genotypes, resulted in a great diversity of hemp genotypes with regard to biological characteristics, adaptability to a range of climate conditions and suitability for specific uses. Availability of a wide range of cultivars of different duration and photoperiod sensitivity leads to uncertainty in prediction of crop development behaviour and management decisions, especially at higher latitudes, as was pointed by Amaducci et al (2012). Experimental evidence regarding ability of different hemp varieties to suppress weeds is scarce and fragmentary.…”
Section: Introductionmentioning
confidence: 99%
“…Under optimal climate conditions, Felina 34 differentiated for its relatively short juvenile phase, only 13 days compared to about 20 days estimated for the other cultivars. The calibration and comparison against independent data revealed that this model was successfully used in decision support for predicting hemp flowering and production under a variety of latitudes (Amaducci et al 2012). Moreover, the strong influence of climate conditions, especially air temperature (Amaducci, Colauzzi, Bellocchi, et al 2008) and rainfall, on flowering time (Venturi 1967;Venturi and Amaducci 1996) may significantly bias the model forecast.…”
Section: Studies On the Relationships Between Flowering And Yieldmentioning
confidence: 99%